Validation of a predictive model for hospital-acquired acute kidney injury with emergence of SARS-CoV-2 variants. (June 2023) - McAdams, Meredith C; Xu, Pin; Li, Michael; Gregg, L Parker; Saleh, Sameh N; Ostrosky-Frid, Mauricio; Willett, Duwayne L; Velasco, Ferdinand; Lehmann, Christoph U; Hedayati, S Susan
We previously developed and validated a model to predict acute kidney injury (AKI) in hospitalized coronavirus disease 2019 (COVID-19) patients and found that the variables with the highest importance included a history of chronic kidney disease and markers of inflammation. Here, we assessed model performance during periods when COVID-19 cases were attributable almost exclusively to individual variants. Electronic Health Record data were obtained from patients admitted to 19 hospitals. The outcome was hospital-acquired AKI. The model, previously built in an Inception Cohort, was evaluated in Delta and Omicron cohorts using model discrimination and calibration methods. A total of 9104 patients were included, with 5676 in the Inception Cohort, 2461 in the Delta cohort, and 967 in the Omicron cohort. The Delta Cohort was younger with fewer comorbidities, while Omicron patients had lower rates of intensive care compared with the other cohorts. AKI occurred in 13.7% of the Inception Cohort, compared with 13.8% of Delta and 14.4% of Omicron (Omnibus p = 0.84). Compared with the Inception Cohort (area under the curve (AUC): 0.78, 95% confidence interval (CI): 0.76–0.80), the model showed stable discrimination in the Delta (AUC: 0.78, 95% CI: 0.75–0.80, p = 0.89) and Omicron (AUC: 0.74, 95% CI: 0.70–0.79, p = 0.37) cohorts. Estimated calibration index values were 0.02 (95% CI: 0.01–0.07) for Inception, 0.08 (95% CI: 0.05–0.17) for Delta, and 0.12 (95% CI: 0.04–0.47) for Omicron cohorts, p = 0.10 for both Delta and Omicron vs Inception . Our model for predicting hospital-acquired AKI remained accurate in different COVID-19 variants, suggesting that risk factors for AKI have not substantially evolved across variants.